Growth performance morphomeristic and genetic characterization of crossbreeding between gift and UPM red tilapia - Francis, Nwachi Oster (2018)
This study was carried out to evaluate the possibility of producing hybrids of different crossing between Genetically Improved Farm Tilapia (GIFT) and UPM red tilapia (Oreochromis sp.) aiming to produce reddish coloured version of new generations of a first filial (F1) reciprocal (nF1), second filial (F2), backcross (BcF1) and its reciprocal (nBcF1). The strains produced were assessed for possibility of inheriting the phenotypic traits of UPM red tilapia and qualitative traits of GIFT, their growth performance in aquarium and fish cages. To prevent misidentification for stock management, morphomeristic traits and mitochondria control region (mtDNA) analyses were carried out for classification and identification. In experiment one, broodstock of UPM red tilapia (Pure 1) and GIFT (Pure 2) were selected based on standard method and paired into the ratio of female to male (3:1) to produce F1 and reciprocal nF1. Offspring of F1 were then selected and used as the parents stock to produce F2 and backcross by mating (UPM red tilapia x F1) to give BcF1 and (GIFT x F1) to give nBcF1. The inheritance trait of body colour of different crossing produced four different phenotypic colourations; reddish colour, red with dark blotches, wild type (dark) and mixed red-wild type of F1, nF1, Pure 1 and Pure 2 with various percentages of reddish colour phenotype. The F2, BcF1 and nBcF1 produced faded wild type, red with dark blotches, red with dark posterior patches and mixed wild type. The highest percentage (64.61%) of reddish colour type were produced from the F1. The successful of the crosses were determined based on the time of fry were produced. Results showed nF1 was produced at a mean time span of 21.93 days after four successful trials compared to 14.53, 14.72 and 14.2 days by the Pure 2, Pure 1 and F1. Similarly the F1 outperform the others by producing a mean total fry of 154.65 compared to Pure 1, Pure 2, and nF1 which were 148.16, 149.37, and 137.77. There is high level of possibility that the body colour of male influenced the female attracted to male based on shorter number of days for the successful of spawning. In experiment two, the growth performance and feed conversion ratio (FCR) of Pure 1, Pure 2, F1 and BcF1 were assesses. The F1 and BcF1 were selected among the other strains that were produced due to ability of these strains producing higher percentage of reddish colour of fry. The experiment was conducted in two culture systems which were aquarium and fish cages. The F1, BcF1 and their base parent (Pure 1 and Pure 2) were stocked at a stocking density of 0.1L-1 with mean body weight and total length of 7.84 g and 7.77 cm in aquarium, 300 tails per cage (3.5m×1.2m×3.5 m) in cages with size of 8.19 g at 8.46 cm in triplicates. Growths were presented in a mean body weight and recorded 332.15 g for F1 compared to 264.69 g, 271.42 g and 320.02 g with the values of FCR 1.1 for pure 1, pure 2 and BcF1, respectively. In aquarium, weight gain of F1 was 40.55 g compared to 33.46 g, 40.87 g and 39.15 g with FCR of 1.38, 1.29 and 1.01 for Pure 1, Pure 2 and BcF1 respectively. The F1 has the highest FCR in both aquariums (1.0) and cages (1.08). Besides, F1 and BcF1 in both systems showed higher growth rate compared to their base parents at a culture days of 52 in aquarium and 150 days in cages. In experiment three, morphomeristic components of Pure 1, Pure 2, F1 and BcF1 were measured based on truss network protocol by measuring 20 morphometric and five meristic components to predict and classified each strain using discriminate analysis (DFA) and principal component analysis (PCA) using SPSS and Unscramble@X statistical tool software. The discriminate coefficient score of upper lip length recorded the highest (.825) among the others, which is for predicting the group at which the strains belong. The pelvic length, lower lip length and cheek depth were at .690, .629, and. 525, while their meristic counts for dorsal fin and anal fin were .993 and .992. Eigen values of three Functions derived were .721, 3.202 and 150.406 in morphometric, and .313 and 1.408 in two Functions for meristic counts as the best predicting for discrimination for each cross. The morphometric predicting components loaded 52% at PC1, 11% for PC2, and 59% at PC1 and 29% for PC2 for the meristic component. The random prediction values for morphometric and meristic were 80, 72, 92 and 96% and 96, 72, 60 and 12% for Pure 1, Pure 2, F1 and BcF1 respectively. This shows that morphometric traits could be used in assigning all the strains to their base parents. However based on meristic traits, BcF1 could not be assigned to their base parents. It can infer that 93% of the prediction correlate correctly classify to the strain using their morphometric trait, while prediction level resulted to correct placing at 60% of meristic traits. In experiment four, identification of Pure 1, Pure 2 their F1 and BcF1 was carried out to evaluate the genetic variability and phylogeny of each strain using mtDNA. Genomic DNA was extracted from each strain (n=26) from 25 mg of muscles tissue using Promega USA test kit. The extracted DNAs were viewed in a gel electrophoresis under ultraviolet light using Gel doc XR system Pc and Mac from USA for the qualitative validation. The extracted DNAs were subjected to polymerise chain reaction (PCR) at their mitochondria control region using ORMT-F 5’- CTAACTCCCAAAGCTAGGAATTCT-3’and ORMT-R 5’- CTTATGCAAGCGTCGATGAAA-3’primer at pre-denaturation step for 940c at 3 min in a cycle of 35, denaturation at 940c for 30 s, annealing at 540C for 40 s, extension at 720C for 40 s and a final extension step of 720C for 10 min. The multiple sequences were aligned with clustalW in BioEdit software. Evolutionary analysis of each strain was conducted with MEGA software using neighbour-joining (NJ) tree, maximum parsimony, and maximum likelihood with control region sequence and out-groups from the same family; (Oreochromis. niloticus (Genbank accession number: KC 811379.1) and (Tilapia zilli (Genbank accession number: AF 3288531). This was constructed with the Kimura 2 parameter distance model. The branching order of the tree was tested by bootstrapping at 1050 replicates data. Pure 1, Pure 2, F1 and BcF1 were found varied based on the variation in the degree of polymorphism. Pure 2 has the highest nucleotide diversity (0.0302) with a total of 4 control regions while the other stains have one single region. Pure 2 has the highest haplotype diversity (0.2933) although, out of five of the haplotype that were observed in the samples of Pure 1, F1 and BcF1 shared one between them. It is of note that the phylogenetic analysis in this study verified monophyletic relationship based on the high value of consistency index (0.805556) and retention index (0.758621). The high level of relatedness with consistence overlap and clustering are linked to the low genetic distance (0.1). Despite the closeness of the strain to each other, their control region analysis reveal a uniqueness that was specific to individuals and could be used for identification Overall F1 and BcF1 that are reddish in colour were able to produce with higher FCR recorded than their parents. Improvement of mean weight gain revealed heterosis of the F1 and BcF1 as a result of qualitative traits from Pure 2. Pure 1 and Pure 2 females showed more attracted to male of same colour or male of reddish colouration during mating. Lastly, every strain could be assigned to their base parents using their predicting components (morphomeristic), and the mtDNA control region was found useful in validated the identity of each strains.